Development and Validation of a Multi-Dimensional Measure of Activity-Based Working Behaviors - Bäcklander, Gisela; Fältén, Rebecca; Bodin Danielsson, Christina; Toivanen, Susanna; Richter, Anne (Frontiers in Psychology, 2021)
Most work on activity-based working centres on the physical environment and digital technologies enabling flexible working. While important, we believe the key components for implementing activity-based working are employee and manager behaviours. To measure the degree of enactment of activity-based work, based on workshops with experienced practitioners as well as previous literature, we have developed and validated a behaviour-focused measure of activity-based working behaviours. In our initial sample (Sample 1 N = 234) three subscales were identified: task – environment crafting, workday planning, and social needs prioritization. In the replication sample (Sample 2 N = 434) this model also showed adequate fit. Moreover, task – environment crafting was related to general health and lower stress in sample 1 (multi organization sample), but not in the single-organization sample (sample 2). Workday planning was associated with higher concentration in both samples and in the second sample with general health and work engagement; the latter was also related to social needs prioritization.